Un encadrement négocié de la rente locative ? Usages ambivalents du « permis de louer » face à la division des pavillons en banlieue de Paris - Benoît Frel-Cazenave (Belgeo)
New instruments are being made available to local authorities in France to regulate the private rental market. This contribution examines one of them, the ‘renting license’, based on a field study conducted in Pierrefitte-sur-Seine, a commune in the northern suburbs of Paris. The article describes the political justifications for introducing such an instrument: faced with the division of suburban housing and its conversion into private rental units, local authorities are seeking to control the development of buildings and limit their deterioration. Landlords are particularly targeted by local government, through the implementation of a ‘renting license’. An analysis of local policies to regulate the rental market shows how local public players anticipate the expectations of landlords in order to win their support for an instrument that is supposed to constrain them.